A Regional Scale Investigation on Groundwater Arsenic in Different Types of Aquifers in the Pearl River Delta, China. (18th February 2018) - Hou, Qinxuan; Sun, Jichao; Jing, Jihong; Liu, Chunyan; Zhang, Ying; Liu, Jingtao; Hua, Mengjian
Abstract : Nearly 400 groundwater samples were collected from different types of aquifers in the Pearl River Delta (PRD), and the concentrations of groundwater arsenic (As) and other 22 hydrochemical parameters in different types of aquifers were then investigated. Results showed that groundwater As concentration was up to hundredsμ g/L in granular aquifers, while those in fissured aquifers and karst aquifers were only up to dozens and severalμ g/L, respectively. Correspondingly, about 9.4% and 2.3% samples with high concentrations (>0.01 mg/L) of As were in granular and fissured aquifers, respectively, but no samples with high concentration of As were in karst aquifers. The source and mobilization of groundwater As in granular aquifers are likely controlled by the following mechanism: organic matter in marine strata was mineralized and provided electrons for electron acceptors, resulting in the release ofN H 4 + andI - and the reduction of Fe/Mn andN O 3 -, and was accompanied with the mobilization of As from sediments into groundwater. By contrast, both natural processes including the competitive adsorption between As anions andF - /P O 4 3 - /H C O 3 - and anthropogenic processes including industrialization were responsible for high concentrations of groundwater As in fissured aquifers.